The Spatial Factor in African History : the Relationship of the Social, Material, and Perceptual. - Howard, Allen M. (African social studies series, 2004)
In this collection authors apply spatial analysis to case studies of social, economic, and political dynamics in West, Central, and East Africa during the nineteenth and twentieth century. Also included is a lengthy essay re-interpreting tropical Africa, 1800-1930, using spatial theory.